Towards managing the evaluation on green hotel initiatives - Jusoh, Yusmadi Yah; Baharom, Salmi; Ban, Ainita; Zakaria, Naurah Malihah; Nordin, Siti Aishah (Universiti Utara Malaysia, 2016)
Nowadays, the ecological concerns have impact to the consumers purchasing behaviour and demand towards environmental friendly products and services. Tourism is one of the industries that hugely depend on the well-being of the environment as tourists travelling millions of miles away to see the environment that are exotic, clean and unpolluted. It is not deniable this industry has also the potential threatening condition of natural environment. Over recent years, there has been an explosive growth of interest in the eco-friendly initiatives on saving the environments. Green initiative is actively implements in many sites of hotel industry businesses. The hotels management is moving forward on supporting the green initiative to keep environment clean in order to minimize the impacts to the environment. This paper presents Green Hotel Initiatives Evaluation System (GHIES) which was developed to help the hotel on managing their green hotel initiatives. The system is capable to measure, evaluate, and provide recommendations and reports to assist the hotel towards better initiatives in the future.